Plan robustness in field junction region from arcs with different patient orientation in total marrow irradiation with VMAT. Issue 7 (November 2015) - Mancosu, Pietro; Navarria, Piera; Castagna, Luca; Reggiori, Giacomo; Stravato, Antonella; Gaudino, Anna; Sarina, Barbara; Tomatis, Stefano; Scorsetti, Marta
Abstract: Background: The cranial-caudal (CC) maximum LINAC couch shift is usually around 130–150 cm; therefore total marrow (and lymph-nodes) irradiation (TMI-TMLI) requires two different plans, one with patient head-first-supine ("body plan" – skull-thighs) and a second feet-first-supine ("legs plan" – feet-femurs head). A challenging planning is required to manage the region in which the radiation come from the two plans (that cannot be automatically optimized together). We studied a robust way to produce a plan sum in this field junction region without creating under/over dosage on PTV and hotspots out. Material and methods: Twenty-one patients candidates to bone marrow transplantation were treated with TMI-TMLI on TrueBeam using RapidArc technique. All body bones were defined as PTV and, for TMLI, lymph-nodes and spleen were included, too. The two plans according to ALARA principle were optimized. In particular, in the overlapping region (PTVJ), two specular sigmoid dosimetric shapes were adopted for obtaining homogeneous integral dose. Furthermore, 144 plans from four patients were calculated to evaluate plan robustness. Results: In all patients, 95% of the prescription dose covered >99% of PTVJ. Regarding the robustness study, differences <1% were found for mean doses to PTVJ and surrounding healthy tissue (HT) for 5 mm shifts. Maximum dose increased up to 21.4% for 10 mm shifts in CC. PTVJ V95% decreased of around 9% (range −3.4% to 24.3%) revealing possible target under-dosage. Conclusions: Dosimetric field junction from two different plans is possible for TMI-TMLI with optimal target coverage. The correct repositioning between the two plans is fundamental, in particular in CC direction. Highlights: TMI is a recent method in substitution of TBI. TMI presents several technical difficulties, challenging for a medical physicist. Two different CTs with different orientations are required to cover the target. A robust method to treat the dosimetric field junction between the two CT series is presented.